Steady performance and dynamic characteristics of a superellipse groove dry gas seal at a high-speed condition. Issue 6 (14th March 2020) - Kou, Guiyue; Li, Xinghu; Wang, Yan; Lin, Mouyou; Tan, Chunsen; Mou, Mingfei
Abstract : Purpose: The purpose of this paper is to enhance film stiffness and control seal leakage of conventional spiral groove dry gas seal (S-DGS) at a high-speed condition by introducing a new type superellipse surface groove. Design/methodology/approach: The steady-state performance and dynamic characteristics of superellipse groove dry gas seal and S-DGS are compared numerically at a high-speed condition. The optimized superellipse grooves for maximum steady-state film stiffness and dynamic stiffness coefficient are obtained. Findings: Properly designed superellipse groove dry gas seal provides remarkable larger steady-state film stiffness, dynamic stiffness coefficient and lower leakage rate at a high-speed condition compared to a typical S-DGS. The optimal values of first superellipse coefficient for maximum steady and dynamic stiffness are 1.3 and 1.4, whereas the optimal values of second superellipse coefficient for which are 1.4 and 2.0, respectively. Originality/value: A new type of molded line, namely, superellipse curve, is proposed to act as the boundary lines of surface groove of dry gas seal, as an alternative of typical logarithm helix. The conclusions provide references for surface groove design with larger stiffness and lower leakage rate at a high-speed condition.